Price Competition in an Inflationary Environment - Peter Dürsch; Thomas Eife (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
A constant price level facilitates cooperation among firms whereas steady inflation and deflation rates lower firms' ability to cooperate. In an experimental market with price competition we show that both inflation and deflation signi cantly reduce cooperation compared to treatments with a constant price level. The diffi culties to cooperate also aff ect prices and welfare: depending on the market structure, inflation and deflation lead to signifi cantly lower real prices and higher welfare.
Keywords: C92; D43; E31; 330